Cocoa Bean Shell—A By-Product with Nutritional Properties and Biofunctional Potential - Rojo-Poveda, Olga (Nutrients, 2020)
Cocoa bean shells (CBS) are one of the main by-products from the transformation of cocoa beans, representing 10%‒17% of the total cocoa bean weight. Hence, their disposal could lead to environmental and economic issues. As CBS could be a source of nutrients and interesting compounds, such as fiber (around 50% w/w), cocoa volatile compounds, proteins, minerals, vitamins, and a large spectrum of polyphenols, CBS may be a valuable ingredient/additive for innovative and functional foods. In fact, the valorization of food by-products within the frame of a circular economy is becoming crucial due to economic and environmental reasons. The aim of this review is to look over the chemical and nutritional composition of CBS and to revise the several uses that have been proposed in order to valorize this by-product for food, livestock feed, or industrial usages, but also for different medical applications. A special focus will be directed to studies that have reported the biofunctional potential of CBS for human health, such as antibacterial, antiviral, anticarcinogenic, antidiabetic, or neuroprotective activities, benefits for the cardiovascular system, or an anti-inflammatory capacity.